Analysis of the Effect of Self Confidence on Students' Mathematical Problem Solving Ability - muzaiyanah, ufiq muzaiyanah (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
This research aims to determine the effect of self confidence on student’s mathematical problem solving abilities. The population in this research was all eighth grade students of SMP Negeri 2 Sewon Bantul in the odd semester of the 2024/2025 academic year. The population in this study were all students in class VIII of SMP Negeri 2 Sewon Bantul for the 2024/2025 academic year. The sample in this research was class VIIIB which was selected using a purposive sampling technique. with a total of 29 students. Research data taken in the form of quantitative data obtained from self-confidence questionnaires and tests of student’s mathematical problem solving abilities. Based on the results of hypothesis testing using linear regression analysis obtained diperoleh nilai 0,501, sehingga persamaan regresi linearnya adalah Ŷ = 55,153 + 0,501X and correlation coefficient, it can be concluded that self-confidence has an effect on student’s mathematical problem solving abilities.